Quantum computing using native interaction in superconducting circuits - Tsunoda, T (2021)
Superconducting circuits form one of the most promising hardware platforms for building a quantum computer. As the quantum computing system gets more complex as we increase the size, employing simple circuit designs and control strategies can make the task of building a large scale quantum computer easier.